Character of National University- A Conceptual Framework - Mittal, L N (Tattva Journal of Philosophy, 2018)
The paper situates India’s global position with respect to its R&D and patent development and then highlights the current status of university system in India as a causative factor since majority of universities are busy in teaching merely how to qualify a paper-pencil test without much impetus on Research and Development. The paper also presents the perceived scenario of a national university and its characteristics. It also suggests ways in which universities can prioritize to produce researchers and innovators.